Risk and sustainability in project management with special reference to the IT sector - Bahaaudeen, Amirah; Nazneen, Afroze; Haque, Rasheedul (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the role of risk analysis in project management, with a focus on sustainability within the information technology (IT) sector. Existing research on agile-managed projects often overlooks the interplay between agile methodologies, risk management practices, and project outcomes. This study emphasizes the critical role of the project team, aligning with the second principle of the Standard for Sustainability in Project Management. Key risk factors identified include technology, hardware, systems, scheduling, and cost. A comprehensive risk management framework for IT projects was developed based on empirical data collected from 233 respondents comprised of 109 expert interviews and 124 survey respondents from structured questionnaires. The model of this study identifies six principal risk domains—organizational culture, schedule/cost, project environment, project team, user/customer, and technological context—which account for 86% of potential risks in IT project lifecycles. Findings highlight that project managers systematically engage in risk recognition, impact assessment, monitoring, and sustainability management. This research contributes both theoretical insights and practical tools to the field of agile IT project risk management.